2001
DOI: 10.1161/hh1401.093575
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Muscle Cell Changes During Flow-Related Remodeling of Rat Mesenteric Resistance Arteries

Abstract: Abstract-To obtain information on the molecular and cellular mechanisms of flow-induced arterial remodeling, we analyzed the morphology and smooth muscle cell (SMC) characteristics in rat mesenteric resistance arteries after interventions that decreased and increased flow. Juvenile male Wistar Kyoto rats were subjected to surgery that, compared with control arteries, provided arteries with chronic low flow and chronic high flow. Low flow resulted in a decreased passive lumen diameter, hypotrophy of the artery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
128
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(139 citation statements)
references
References 44 publications
9
128
2
Order By: Relevance
“…Studies have demonstrated that a sudden increase in blood flow initiates an enlargement of the arterial lumen that progresses for months as the WSS tends to a homeostatic or normal level (23,25). A gradual increase in blood flow has been reported by several groups to result in outward hypertrophic remodeling of resistance (4,41,44,45,47) and conductive arteries (25,36,39). The flow-induced remodeling may be an attempt to maintain mechanical homeostasis (24,25).…”
mentioning
confidence: 99%
“…Studies have demonstrated that a sudden increase in blood flow initiates an enlargement of the arterial lumen that progresses for months as the WSS tends to a homeostatic or normal level (23,25). A gradual increase in blood flow has been reported by several groups to result in outward hypertrophic remodeling of resistance (4,41,44,45,47) and conductive arteries (25,36,39). The flow-induced remodeling may be an attempt to maintain mechanical homeostasis (24,25).…”
mentioning
confidence: 99%
“…The three-dimensionaldissector technique is more accurate to determine changes in cell number and size than the more rapid counting of nuclear profiles on hematoxylin-eosin-stained tissue sections. 9 Additional measurement of local transmural pressure and local blood flow at the various time points would have allowed to speculate on the extent to which normalization of wall stress and wall shear stress is impaired in mesenteric resistance arteries of DOCA-salt hypertensive rats. Figure 4 Schematic overview of changes in arterial lumen diameter and medial mass in relation to hypertension (blue arrow), imposed changes in flow (green arrow (high flow) and red arrow (low flow)), SOL1 treatment during hypertension (HT þ SOL-1: orange arrow) and age (purple arrow).…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with the flow-induced outward hypertrophic remodeling reported previously. 9,27,30,31 It was, however, not accompanied by alterations in arterial wall stiffness (Figure 2g), the elastin to collagen ratio or the macrophage count (Table 1). Surprisingly, after 7 weeks exposure to elevated blood flow, the outward remodeling (Figure 1b) and the increases in lumen diameter (Ø: to 455±21 mm, NS, Figure 2b), in medial mass (mCSA: to 14±1 Â 10 3 mm 2 , NS, Figure 2d) and the hyperplasia (# nuclei: to 41±3, NS; Figure 2f), were no longer statistically significant compared with control (NF) arteries of the same normotensive rats.…”
Section: Flow-related Arterial Remodeling In Normotensive Ratsmentioning
confidence: 93%
See 2 more Smart Citations